Growth, survival, and morphometric relationships of Crassostrea corteziensis cultivated during the nursery stage in oyster bags at different tidal levels, in Boca de Camichín, Nayarit, Mexico - Alfonso N Maeda-Martínez; Avicenia G García-Murillo; Daniel Espinosa-Chaurand; Rodolfo Garza-Torres; Ricardo García-Morales (Ciencias Marinas, 2023)
The optimal tide height at which the intertidal oyster bed system (IOBS) should be installed to cultivate Crassostrea corteziensis in Boca de Camichín (BC), Nayarit, Mexico, during the intermediate grow-out stage (39.3–60.2 mm in shell length) was determined. Temperature, salinity, chlorophyll a (Chla), and turbidity were recorded 3 times a day. A trophic state index (TSI) was calculated with Chla and turbidity data. Three treatments corresponding to tide levels were tested: (1) high level (14 cm above mean sea level [MSL], emersion time [ET] = 56.4% of the total duration of the experiment), (2) intermediate level (MSL, ET = 48.6%), and (3) low level (41 cm below MSL, ET = 32.1%). Gross growth rates and absolute and relative monthly growth rates were calculated to identify periods with highest growth relative to environmental conditions. Finally, the effect of the treatments on the dimensions and weight of the oysters was studied. The results indicate that BC water was mesotrophic in April–June and eutrophic in July–August. The low tide level was the best for IOBS operation, with growth rates of 0.15, 0.10, and 0.07 mm·d–1 in shell length, width, and thickness, respectively, and 0.204 g·d–1 wet weight. Cumulative mortality was lower in the low (18.5%) and intermediate (16.4%) treatments. Shell thickness was significant reduced (P < 0.05) in the high treatment and total wet weight was reduced in the high and intermediate treatments. The results of this study offer a viable and different alternative to the cultivation of C. corteziensis in strings that is currently carried out in Boca de Camichín, Nayarit, Mexico.